INFORMATIONAL SUPPORT OF THE USE OF STANDARDS IN E-LEARNING - Oleg I. Selivantsev; Maxim V. Sutyagin (Открытое образование (Москва), 2016)
The article presents tools for information support of the application of standards in the field of e-learning and automate the process of assessing the quality of electronic educational resources. Specifically database of reference quality criteria.